Coastal Clean Water Crisis: How Coastal Communities are Coping with Limited Access to Clean Water - Nurhayati, Nurhayati; Sari, Nailla Deswita; Heliani, Raisah; Nur Wahdan, Muhamad Habib (PROMOTOR, 2024)
This discussion addresses the water crisis in coastal areas, analyzing how local communities cope with limited access to clean water. In daily life, water issues in coastal regions are severe, necessitating that communities manage and adapt to the water crisis to ensure usability. This research aims to analyze how coastal communities endure and address the water crisis. The study employs qualitative research with a descriptive method. Data for this research were obtained through observation, in-depth interviews, and documentation, with researchers conducting fieldwork to collect data. Data analysis techniques used include the Miles and Huberman method. The results indicate that the clean water crisis in coastal areas is caused by several factors, and communities have developed various strategies to overcome limited access to clean water. However, there are numerous challenges faced, requiring communities to find solutions.